A dual-mode biosensor combining transition metal carbonyl-based SERS and a colorimetric readout for thiol detection. Issue 41 (10th October 2019) - Lin, Duo; Zhou, Jiahui; Yu, Yun; Chen, Weiwei; Liao, Pei-Hsuan; Huang, Hao; Kong, Kien Voon
Abstract : A fast SERS and colorimetric dual-modal assay for thiol detection was developed using a triosmium carbonyl cluster as a smart probe. Abstract : A fast SERS and colorimetric dual-modal assay for thiol detection was developed using an unsaturated triosmium carbonyl cluster, Os3 (CO)10 (μ-H)2, as a detection probe. The cluster undergoes a distinct color change in the presence of thiol and the SERS spectrum shows a shift in the CO stretching vibration, located in a silent region where there is no interference from biomolecules. Such assay offers high sensitivity with a detection limit up to 0.1 μM by SERS.